Openness buffers the impact of Belief in Conspiracy Theories on COVID-19 vaccine hesitancy: Evidence from a large, representative Italian sample. (July 2023) - Li, Tania Y.; de Girolamo, Giovanni; Zamparini, Manuel; Malvezzi, Matteo; Candini, Valentina; Calamandrei, Gemma; Starace, Fabrizio; Zarbo, Cristina; Götz, Friedrich M.
Abstract: As COVID-19 continues to incur enormous personal and societal costs, widespread vaccination against the virus remains the most effective strategy to end the pandemic. However, vaccine hesitancy is rampant and has been steadily rising for decades. Seeking to remedy this, personality psychologists have begun to explore psychological drivers of vaccine hesitancy, including the Big Five. Openness to Experience presents itself as a vexing case as previous attempts to study its association with vaccine hesitancy have yielded mixed findings. In this preregistered study, we hypothesise that the impact of Openness to Experience on Vaccine Hesitancy depends on its interplay with other factors, namely conspiracy beliefs. To test this, we apply logistic regressions, simple slopes analyses, and propensity score matching to a nationally representative sample of 2500 Italian citizens, collected in May 2021. Contrary to our original hypothesis (i.e., Openness will have a positive association with Vaccine Hesitancy at high – and a negative at low – levels of Conspiracy Beliefs) we find that high Openness diminishes the impact of Belief in Conspiracy Theories on Vaccine Hesitancy. Consistent with previous research, we propose that Openness serves as a buffer against extreme positions by allowing individuals to be exposed to a greater diversity of information. Highlights: We examine Openness and Vaccine Hesitancy in a big, representative Italian sample. Openness reduces the effect of Belief in Conspiracy Theories on Vaccine Hesitancy. Openness may prevent extreme beliefs by promoting access to diverse information.